Exploring intercultural interaction: the use of semiotic resources in meaning-making process. - Abdullah, Nur Nabilah; Sahar, Rafidah (2020)
Intercultural communication refers to interaction between speakers of different backgrounds such as different linguistic and cultural origins (Kim, 2001). Interaction in face-to face situations has demonstrated that spoken language involves both verbal and an array of semiotic resources for social action. Semiotic resources that include use of talk, gestures, eye gaze and other nonverbal cues can convey semantic content and can be a crucial point in a conversation (Hazel et al., 2014). Drawing from the conversation analytic (CA) approach, we explored how participants employed semiotic resources in word searches activity in an intercultural context. Word searches are moments in interaction when a speaker’s turn is temporarily ceased because the speaker displays difficulty searching for appropriate linguistics items in formulating the talk (Schegloff et al., 1977; Kurhila, 2006). In this research, naturally occurring interactions in a multilingual setting were video recorded. The participants were Asian university students with different first language backgrounds. The findings suggested that multilingual participants mutually collaborate by utilizing verbal, gaze, gestures and other nonverbal cues as useful semiotic resources in the meaning-making process to resolve word searches and achieve mutual understanding in intercultural interaction.